Models of Plankton Community Changes during a Warm Water Anomaly in Arctic Waters Show Altered Trophic Pathways with Minimal Changes in Carbon Export - Vernet, Maria; Richardson, Tammi L.; Metfies, Katja; Nöthig, Eva-Maria; Peeken, Ilka (Frontiers in Marine Science, 2017)
Carbon flow through pelagic food webs is an expression of the composition, biomass and activity of phytoplankton as primary producers. In the near future, severe environmental changes in the Arctic Ocean are expected to lead to modifications of phytoplankton communities. Here, we used a combination of linear inverse modeling and ecological network analysis to study changes in food webs before, during, and after an anomalous warm water event in the eastern Fram Strait in the West Spitsbergen Current that resulted in a shift from diatoms to flagellates during the summer (June-July). The model predicts wide-ranging differences in carbon flow with diatom- versus Phaeocystis/nanoflagellate-dominated phytoplankton communities, but relatively small differences in carbon export. The model suggests a change in the zooplankton community and activity by increasing microzooplankton abundance and by switching meso- and macrozooplankton feeding from strict herbivory to omnivory, detritivory and coprophagy. When small cells and flagellates dominate, the phytoplankton carbon pathway through the food web is longer and the microbial loop is more active. Furthermore, one step is added in the flow from phytoplankton to mesozooplankton and phytoplankton carbon to higher trophic levels is available either as detritus or as microzooplankton biomass. Model results highlight how specific changes in phytoplankton community composition, as expected in a climate change scenario, do not necessarily mean a reduction in carbon export.